A multi-center clinical study comparing Sansure Magb and CAP/CTM HBV tests in the quantitative detection of HBV DNA - Xiaoyu Fu; Deming Tan; Xiaoguang Dou; Jinjun Chen; Juan Wu (Journal of Infection in Developing Countries)
Introduction: As the most reliable means of diagnosing hepatitis (HBV) infection and predicting the prognosis of HBV-related chronic liver disease, the COBAS AmpliPrep/COBAS TaqMan real-time polymerase chain reaction (PCR) (CAP/CTM) assay provides a highly sensitive and accurate method for quantifying HBV DNA. However, the high cost of the COBAS reagents is prohibitive in many developing countries. Thus, we compared the Sansure magnetic bead (Magb) assay, a novel technology developed by a Chinese company, with the CAP/CTM assay. Methodology: The reproducibility and sensitivity of the Sansure Magb assay were first validated using HBV DNA reference samples. Next, the quantitative results for the two assays using 635 blood samples collected from chronic hepatitis B patients and 10 healthy controls were compared. Results: The Sansure Magb assay showed high reproducibility and was at least as sensitive and specific as the CAP/CTM assay. Among the patient samples, 407 tested positive by both methods, with 386 (94.84%) showing quantitative differences of less than 1 log unit and 21 (5.16%) showing quantitative differences of between 1 and 2 log units. The results from the assays were closely correlated. Bland-Altman plot analysis showed that only 6.6% of the data points fell outside the 95% limits of agreement, which suggests that the differences between methods are clinically acceptable. Conclusions: This study demonstrates that the Sansure Magb assay is highly sensitive and reproducible. Based on its reduced cost, the Sansure Magb assay may be more applicable than the CAP/CTM assay for HBV diagnosis in developing countries such as China.